Prediction of results of female paraswimmers in freestyle disciplines at Tokyo 2020 Paralympics - Mojsilovic. A.; Tsismalidou, A.; Doulgeridis, P.; Projovic, A.; Hadcovic, M.; Kostic, S.; Aleksandrovic, M. (Book of Proceedings Fis Communications 2019, 2019)
The aim of the research was to determine the trend in the development of the results of female paraswimmers who won medals in freestyle disciplines in the last five Paralympic Games (POG) and the formation of a prediction result model at the next Tokyo 2020 POG. First of all, a database of the best results on the last five POG in all classes was created. After that, the equation of the trend and the results (times) that the female paraswimmers are to achieve are calculated in order, hypothetically, to win the appropriate medal at the next POG. Due to the lack of continuity of some disciplines, the results for classes S1, S2, S3, S4 and S14 were not processed. The trend of development of results on the POG for the class of S5, S6, S7, S8, S9, S10, S11, S12 and S13 in the freestyle has been determined. The significance of this research is that the problem of women in the Paralympic sport is being addressed, which is a rarity in the previous research. Also, the results and the conclusion of this research provide a (mathematical) response to coaches of para-]swimmers, and that is the result of which their female para-swimmer must swim in order to expect a medal at the next Tokyo 2020 POG.